Holding wild caught red king crab, Paralithodes camtschaticus: effects of stocking density and feeding on survival and meat content. (28th July 2014) - Siikavuopio, Sten Ivar; James, Philip; Olsen, Bjørn Ronald; Evensen, Tor; Mortensen, Atle
Abstract: In this study, the effects of different stocking densities on survival, injury and meat content of captive male red king crab (mean weight = 2.6 kg) were examined. The first experiment was carried out in square plastic tanks with stocking densities of 100, 150 and 200 kg m −3 for 56 days. In a second experiment, king crabs were kept at a stocking density of 60 kg m −3 and were either fed or not fed. Both mortality and occurrence of injuries increased significantly with increasing stocking density. In the highest density groups, mortality and frequency of injury was 17% and 14% respectively, compared with 5% and 4% in the 150 kg m −3 group. The percentage meat content was significantly lower at the final census compared with the initial census in all stocking density groups. In Experiment 2, there were no mortalities or injuries in either the fed or unfed treatments. The average percentage meat content increased in the fed treatment and decreased in the starved treatments. The results show that adult male king crab can maintain high survival rates at stocking densities up to 150 kg m −3 in holding facilities of the design used in the present study for periods up to 2 months. However, to reduce mortality and frequency of injury over this period densities as low as 60 kg m −3 and a holding system with a large bottom surface area are recommended.